1991
DOI: 10.1073/pnas.88.12.5340
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two genes for 1-aminocyclopropane-1-carboxylate synthase in tomato fruits.

Abstract: ABSTRACT1-Aminocyclopropane-l-carboxylate synthase (ACC synthase; S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 24 publications
4
98
0
Order By: Relevance
“…ACS gene analysis of higher plants indicated that the ACS enzyme is encoded by a highly divergent multigene family, the members of which are subject to differential regulation by more than one inducer (Felix et al, 1991;Olson et al, 1991;Rottmann et al, 1991;Kim et al, 1992;Liang et al, 1992;Yip et al, 1992;Abel et al, 1995). However, in tomato at least two of the six members of the ACS gene family are responsible for the burst of ethylene production during fruit ripening (Lincoln et al, 1993), whereas expression of three of them can be strongly induced by an elicitor (Oetiker et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ACS gene analysis of higher plants indicated that the ACS enzyme is encoded by a highly divergent multigene family, the members of which are subject to differential regulation by more than one inducer (Felix et al, 1991;Olson et al, 1991;Rottmann et al, 1991;Kim et al, 1992;Liang et al, 1992;Yip et al, 1992;Abel et al, 1995). However, in tomato at least two of the six members of the ACS gene family are responsible for the burst of ethylene production during fruit ripening (Lincoln et al, 1993), whereas expression of three of them can be strongly induced by an elicitor (Oetiker et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…c D N k encoding the first of these, ACC-synthase, have been cloned by several groups (Nakaiima et a/., 1990;Olson et a/., 1991;SatoandTheologis, 1989;Sat0 eta/., 1991;Van Der Straeten eta/., 1990). AcDNA, pTOM 13, encoding the ethylene-forming enzyme (EFE), which catalyses the last step in the ethylene biosynthetic pathway was identified on the basis of inhibition of EFE activity in transgenic tomato plants expressing an antisense gene constructed from this clone (Hamilton eta/., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These genes have been isolated and structurally characterized and are differentially expressed in various tissues at different stages of development and in response to internal or external stimuli such as ripening, senescence, wounding, and auxin (Fluhr and Mattoo, 1996). In tomato fruit a large body of evidence demonstrates that massive ethylene production is responsible for increases in LE-ACS2, LE-ACS4, and LE-ACO1 transcripts (Van Der Straeten et al, 1990;Olson et al, 1991;Rottmann et al, 1991;Yip et al, 1992;Lincoln et al, 1993;Barry et al, 1996). Expression of these genes in preclimacteric tomato fruit is rapidly induced and/or enhanced by treatment with ethylene (Maunders et al, 1987;Rottmann et al, 1991;Lincoln et al, 1993).…”
mentioning
confidence: 99%